Report of Virtual Conference. BASICS Phase I - Achievements and Learnings Meeting. May 18-19, 2020 - Bentley, J.W.; Nitturkar, H.; Friedmann, M.; Thiele, Graham (2020)
The Building an Economically Sustainable Integrated Cassava Seed System in Nigeria (BASICS) project began in 2016 and formally ends on 30 June 2020. The project has made progress in demonstrating that commercially viable production and sale of breeder, foundation and certified seed is possible. Furthermore, the project has established a strong basis for building a sustainable seed system by developing building blocks across the seed value chain. This meeting had the following objectives: 1. To identify the achievements and lessons learned in each of the project components; 2. To identify the shortcomings in each component (what would I do differently, knowing what I know now?), remaining challenges and ideas to overcome them; 3. To assess and discuss the challenges and progress made in integrating the components into an integrated seed system and identify ways integration can be improved; 4. To assess and discuss the commercial sustainability of the seed system and identify options to promote its sustainability and further scaling; and 5. To make plans for the publication of the findings and lessons learned during BASICS-1